PERLINDUNGAN HAK ATAS MEREK - Faradz, Haedah (Faculty of Law, Universitas Jenderal Soedirman, 2008)
Along with fast progressively growth of inter-states service and goods commerce, it needed the existence of international arrangement that giving protection guarantee and rule of law in brand area. For the agenda of giving protection to the owner of brand, governmental have renewed Law Number 21 Year 1961 and replace with Law Number 19 Year 1992. Along with ratifying of WTO which loading rule of Trade Related Aspects of Intellectual Property (TRIPS), Indonesia conducted Law Number 19 Year 1992 through Law Number 14 Year 1997 and renewed again with Law Number 15 Year 2001. Because of Indonesia taking part in WTO and agreement of TRIPS, hence Indonesia have to correspond to the rule, as consistency step to ratification which have been conducted by Indonesia, hence change the law and forming new law as a step that must be taken. An application of registration of brand will be accepted if the requirement has been fulfilled as stated in the law of brand. Main requirement which at the same time become especial characteristic of brand is the existence of distinguishing energy. Keyword: Protection, Rights of Brand.